Relationship Between CT Head Findings and Long-term Recovery in Children with Complicated Mild Traumatic Brain Injury. (2nd January 2022) - Hansen, Colby; Waller, Laura C.; Brady, Dalton; Teramoto, Masaru
ABSTRACT: Primary Objective: Complicated mild traumatic brain injury (C-mTBI) refers to CT positive patients with clinically mild TBI. This study investigates the association between CT head findings at time of injury and recovery of paediatric patients with C-mTBI. Research Design: Retrospective survey and chart review. Methods: For paediatric patients with C-mTBI ( N = 77), CT findings associated with corresponding degree and lengths of recovery from C-mTBI using logistic regression analysis. Results: There was a trend that the odds of incomplete recovery at the time of survey was higher for older children than for younger children (OR = 1.14, 95% CI = 0.98–1.32, p = 0.072). There was a trend that the odds of incomplete recovery (OR = 6.26, 95% CI = 0.97–40.57, p = 0.054) and longer duration for recovery (OR = 8.14, 95% CI = 0.78–84.46, p = 0.079) was higher for children with multiple haemorrhagic contusions than those with single haemorrhagic contusion. No other imaging patterns predicted degree or length of recovery with statistical significance ( p > 0.05). Conclusions: Other than the presence of multiple haemorrhagic contusions, no other pattern of imaging abnormality in paediatric C-mTBI appears to be associated with degree or length of recovery. Further studies with larger cohorts are encouraged.